Konsep Pengembangan Clinical Legal Education Berbasis Pendekatan Yang Berkeadilan - Made Oka Cahyadi Wiguna (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Currently, the implementation of legal education in Indonesia has completed by including Clinical Legal Education (CLE). Legal higher education is expected to prepare law graduates who do not only serve as guardians of laws or the rule of law or, more extreme, known as (la bouche de la loi). Consequently, such law enforcement will only be subject to established procedures. Thus, a CLE development concept is needed that prepares lawyers who are committed to substantial justice. To development concept of developing CLE based on an equitable legal approach. The conclusion that can be conveyed is that the ideal CLE to apply is to use a doctrinal approach that puts forward a juridical-philosophical approach. This approach uses an analysis of the basic tenets of a norm to realize the settlement of legal cases based on the values of justice. In addition to the doctrinal approach, introduce a non-doctrinal approach that is based on the constructivism paradigm. Law in this approach is conceptualized contextually, relatively or plurally based on social, individual, local and specific experience. With this approach, it is hoped that later the values of justice will be realized as the main goal, in solving legal problems faced by them.